TINJAUAN PEMANFAATAN KECERDASAN BUATAN: PEMBELAJARAN MANDIRI PADA KETERAMPILAN BAHASA INDONESIA - Feriyanti, Yang Gusti; Judijanto, Loso; Prananda, Gingga; Sanulita, Henny; Kadiyo (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The research carried out aims to review the use of artificial intelligence in independent learning of Indonesian language skills. The research was carried out using a library study approach which included a series of activities related to the use of library data collection methods, reading and retrieval and processing of research materials. In this research, the data sources are books, journals or internet-based websites that contain the topic or discussion being researched. The data sources in this research include 30 references based on topics raised related to the use of artificial intelligence in independent learning of Indonesian language skills. Language skills include 4 abilities, namely listening, speaking, reading and writing. Writing skills are a reference in language skills which must be mastered by students because with writing activities students can express various imaginations or thoughts in writing. Duet AI can help students write essays, reports and other assignments better through the ‘help me write’ feature in Google Docs. First, Duet AI can help students improve their grammar and writing style. Their writing can be identified and corrected for errors in grammar, punctuation, and spelling. Duet AI can also provide feedback on the clarity of their writing. Second, Duet AI can help students develop their own unique writing style. Duet AI will provide feedback on the authenticity and creativity of their writing. It can also help them identify and avoid clichés and overused phrases